Disentangling the effects of the aqueous matrix on the potential toxicity of liquid pig manure in sub-tropical soils under semi-field conditions - Segat J.C.* (2019)
© 2018 Elsevier Inc.Inadequate application of liquid pig manure (LPM) may pose risks to the soil due to the potential contaminants that exists, as well as by the large water input that can originate excessive moisture. By using Terrestrial Model Ecosystems, this study aimed to evaluate the effect of application of LPM (82% moisture) using the application rates of 20, 50 and 150 m3 ha−1 and also of the corresponding amount of water to understand the origin of effects on the soil fauna of two sub-tropical soils. In general, the results obtained for the two soil types indicated that LPM (150 m3 ha−1) changed the composition of soil fauna, with an increase in the abundance of insect larvae and dipterans, but a decrease in the number of earthworms and enchytraeids. Microbial biomass, soil respiration and the nutrients Mg, K and P increased with the amount of LPM supplied to the soil. When analysing the effects of adding large volumes of water via the LPM, results showed that application did not originate significant effects on the parameters measured. The differences obtained when comparing both treatments were mainly attributed to the organic load brought by the LPM and not to the amount of water without LPM.